Environmental Regulation and foreign trade: An analysis for the CAN and MERCOSUR trade blocs in the period 2001-2019 - Alan Fairlie Reinoso; Tania Paredes Zegarra; Paula Paredes Quintana (Journal of Applied Economics, 2024)
This study examines the impact of trade and environmental agreements on trade in the Andean Community (CAN) and the Southern Common Market (MERCOSUR) during the period 2001-2019. Using a panel data methodology, the study analyses the effects of ratifying a number of agreements (the Paris Agreement, the Kyoto Protocol, the Nagoya Protocol, and Free Trade Agreements with the European Union) on total exports and imports. The results reveal that environmental regulations have a differentiated impact on the exports and imports of both trade blocs. These findings underscore the importance of trade and environmental agreements in promoting sustainable trade and emphasize the need for ongoing monitoring of their implementation to foster equitable and sustainable growth in the region.
Keywords: 330; andean community; Environmental regulation; MERCOSUR; regional environmental agreements